2020
DOI: 10.1093/rheumatology/keaa327
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and risk of interstitial lung disease and respiratory failure in rheumatoid arthritis: a nationwide population-based study

Abstract: Objectives MTX is the most commonly recommended DMARD for first-line treatment of RA, however, it has been hypothesized to cause lung disease as an adverse effect. We investigated the risk of interstitial lung disease (ILD) and acute and chronic respiratory failure in persons with RA treated with MTX and other medications. Methods From the Danish National Patient Register (NPR) and the DANBIO register for rheumatic diseases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 19 publications
2
22
0
3
Order By: Relevance
“…Although MTX-induced ILD is well-established by many studies, there is some emerging conflicting evidence suggesting no association between MTX and RA-ILD ( 108 ). For example, a study of MTX use and the risk of ILD in RA patients demonstrated that there was no further increase in risk associated with MTX treatment ( 109 ). Other studies have also reported similar findings suggesting that MTX may delay the onset of ILD ( 110 , 111 ).…”
Section: Pathogenesis Of Ctd-ildmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MTX-induced ILD is well-established by many studies, there is some emerging conflicting evidence suggesting no association between MTX and RA-ILD ( 108 ). For example, a study of MTX use and the risk of ILD in RA patients demonstrated that there was no further increase in risk associated with MTX treatment ( 109 ). Other studies have also reported similar findings suggesting that MTX may delay the onset of ILD ( 110 , 111 ).…”
Section: Pathogenesis Of Ctd-ildmentioning
confidence: 99%
“…The types of pulmonary manifestations may vary by underlying CTD diagnosis ( Table 2 ). The prevalence and mortality of ILD for each CTD are different, and the prevalence of ILD secondary to various CTDs varies as follows: 1 to 15% in SLE ( 106 ), 6.5 to 33% in RA ( 107 , 108 ), 19.9 to 86% in PM/DM ( 109 , 110 ), 86% in anti-Jo-1 positive patients ( 111 ), 40 to 91% in SSc ( 112 , 113 ), 47 to 90% in MCTD based on radiologic feature ( 108 , 114 ), and 9 to 20% in SS ( 115 ). Related reports indicate the mortality of ILD is 20% in RA-ILD ( 116 , 117 ), 12 to 44% in PM/DM ( 118 ), and a 10-year mortality of up to 40% in SSc ( 119 ).…”
Section: Clinical Characteristics Of Ctd-ildmentioning
confidence: 99%
“…In this cohort higher rates of RA-ILD were found in those who had never taken MTX (4.8%) compared with those who had (2.5%), and MTX use was associated with a longer time to the development of ILD. Several other studies have further supported these findings [38][39][40][41]; therefore, MTX should no longer be routinely discontinued in the rheumatoid patient with well-controlled joint disease who develops ILD.…”
Section: Rheumatoid Arthritismentioning
confidence: 86%
“…Im Gegenteil, bei Patienten mit RA zeigte sich ein selteneres und späteres Auftreten einer RA-ILD und eine geringere Mortalität, wenn diese mit MTX behandelt wurden. Es darf bei noch limitierter Datenlage also davon ausgegangen werden, dass MTX Häufigkeit und Verlauf einer ILD positiv beeinflusst, zumindest bei Patienten mit RA [25][26][27].…”
Section: Konventionelle Immunsuppressivaunclassified